The Minamata Convention on Mercury: Attempting to address the global controversy of dental amalgam use and mercury waste disposal - Mackey, Tim K.; Contreras, John T.; Liang, Bryan A. (The Science of the total environment, 2014)
In October 2013, a new international binding treaty instrument called the Minamata Convention on Mercury opened for signature in Minamata City, Japan, the site of arguably the worst public health and environmental disaster involving mercury contamination. The treaty aims to curb the significant health and environmental impacts of mercury pollution and includes provisions addressing the mining, export and import, storage, and waste management of products containing mercury. Importantly, a provision heavily negotiated in the treaty addresses the use of dental fillings using mercury amalgam, an issue that has been subject to decades of global controversy. Though use of dental amalgam is widespread and has benefits, concerns have been raised regarding the potential for human health risk and environmental damage from emissions and improper waste management. While the Minamata Convention attempts to address these issues by calling for a voluntary phase-down of dental amalgam use and commitment to other measures, it falls short by failing to require binding and measurable targets to achieve these goals. In response, the international community should begin exploring ways to strengthen the implementation of the dental amalgam treaty provisions by establishing binding phase-down targets and milestones as well as exploring financing mechanisms to support treaty measures. Through strengthening of the Convention, stakeholders can ensure equitable access to global oral health treatment while also promoting responsible environmental stewardship. •The Minamata Convention on Mercury is a new global health and environment treaty.•The Convention calls for a phase down of dental fillings using mercury amalgam.•It includes voluntary measures but fails to establish binding targets on a phase down.•Future review should include exploration of ways to strengthen implementation.•Strengthening the Convention ensures oral health access and environmental stewardship.